Optimalisasi Kesadaran Masyarakat terhadap Pinjaman dan Alokasi Investasi untuk Pendidikan Anak: Upaya Peningkatan Literasi Keuangan: Optimization of Community Awareness on Loans and Investment Allocation for Children's Education: Efforts to Improve Financial Literacy - Rosalina, Rita; Shabihah, Khansa; Maulidina, Nadhiya Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Improving community financial literacy, especially related to online loans and children's education planning, is an important step to overcome economic challenges in Pedurungan Lor Village. The low level of community understanding of the risks of online loans and the lack of educational investment planning often become barriers to wise financial management. This study aims to improve community financial literacy through an interactive educational workshop. With a quantitative and qualitative approach, this activity includes a pre-test and post-test to measure changes in community understanding, as well as lecture and discussion sessions to provide practical insights. The results showed a significant increase in community awareness of the risks of online loans and the importance of educational investment. The average score of awareness of online loans increased from 2.6 (less agree) in the pre-test to 4 (agree) in the post-test. Community understanding of educational investment also increased, as indicated by the average score changing from 3 (less agree) to 4 (agree). This workshop succeeded in providing concrete solutions and financial management strategies that can be applied to support child education in poverty. In conclusion, community-based financial literacy education is effective in improving community understanding and empowering them to make wiser financial decisions. Similar activities with a sustainable approach and use of digital media are recommended to reach more participants and deepen community understanding.